(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Pain management after liver surgery is the key point to enhance postoperative recovery. Subjects and research methods: 7 patients in descriptive research were underwent liver surgery, ASA I-II from July 2023 to July 2024 in Viet Duc University Hospital. Results: The average age was 53 years old, the youngest was 11, the oldest was 69. ASA II 86%, 6 men, 1 woman. The mean VAS score at rest was less than 2. The VAS score with movement was 2-3 on the first day. In the following days, VAS score range at 1-2. Medium duration was 9.5 minutes, average catheter length was 6.2 cm. No complication was reported. Conclusion: The method of external oblique intercostal block showed good effectiveness in the initial steps, without complications and is technically feasible.